Effects of mitotane on the hypothalamic–pituitary–adrenal axis in patients with adrenocortical carcinoma. Issue 4 (October 2017) - Reimondo, Giuseppe; Puglisi, Soraya; Zaggia, Barbara; Basile, Vittoria; Saba, Laura; Perotti, Paola; De Francia, Silvia; Volante, Marco; Zatelli, Maria Chiara; Cannavò, Salvatore; Terzolo, Massimo
Abstract : Objective: Mitotane, a drug used to treat adrenocortical cancer (ACC), inhibits multiple enzymatic steps of adrenocortical steroid biosynthesis, potentially causing adrenal insufficiency. Recent studies in vitro have also documented a direct inhibitory effect of mitotane at the pituitary level. The present study was aimed to assess the hypothalamic–pituitary–adrenal axis in patients with ACC receiving mitotane. Design and methods: We prospectively enrolled 16 patients on adjuvant treatment with mitotane after radical surgical resection of ACC, who underwent standard hormone evaluation and h-CRH stimulation. A group of 10 patients with primary adrenal insufficiency (PAI) served as controls for the CRH test. Results: We demonstrated a close correlation between cortisol-binding globulin (CBG) and plasma mitotane levels, and a non-significant trend between mitotane dose and either serum or salivary cortisol in ACC patients. We did not find any correlation between the dose of cortisone acetate and either ACTH or cortisol levels. ACTH levels were significantly higher in patients with PAI than that in patients with ACC, both in baseline conditions (88.99 (11.04–275.00) vs 24.53 (6.16–121.88) pmol/L, P = 0.031) and following CRH (158.40 (34.32–275.00) vs 67.43 (8.8–179.52) pmol/L P = 0.016). Conclusions: The observation of lower ACTH levels in patients with ACC than that in patients with PAI, both in basal conditions and after CRH stimulation, suggests that mitotane may play an inhibitory effect on ACTH secretion at the pituitary levels. In conclusion, the present study shows that mitotane affects the HPA axis at multiple levels and no single biomarker may be used for the assessment of adrenal insufficiency.